Electricity pricing using a periodic GARCH model with conditional skewness and kurtosis components - Ioannidis, Filippos; Kosmidou, Kyriaki; Savva, Christos S.; Theodossiou, Panayiotis (My University, 2021)
This paper extends the investigation of the stochastic properties of electricity price growth rates beyond their first two conditional moments allowing for the impact of seasonality on their parameters. The main contributions include the breakdown of electricity price risk into its pure and skewness price components and the development of a risk neutral forecasting equation for electricity prices. Empirical results using ten-years of hourly wholesale prices from the Day-Ahead electricity market in Germany depict the presence of seasonality, strong mean reversion and up-to third degree time-varying moments.
Keywords: Risk analysis; Asymmetric volatility; Pure and skewness price of risk; Risk neutral equilibrium electricity prices; Skewed generalized error distribution